The future of employment : how susceptible are jobs to computerisation? - Frey, Carl Benedikt [Verfasser]; Osborne, Michael A. [Verfasser] (My University, 2013)
"We examine how susceptible jobs are to computerisation. To assess this, we begin by implementing a novel methodology to estimate the probability of computerisation for 702 detailed occupations, using a Gaussian process classifier. Based on these estimates, we examine expected impacts of future computerisation on US labour market outcomes, with the primary objective of analysing the number of jobs at risk and the relationship between an occupations probability of computerisation, wages and educational attainment." (Authors' abstract, BIBB-Doku)
Keywords: G 2.2.1 Technologisierung; I 2.3.2 Nordamerika; Digitalisierung; Arbeitsmarkt; Substitutionseffekte; USA